Deutsch als "leicht zu erlernende Fremdsprache" - Kurtz, Gunde (Linguistik Online, 2005)
The goal of this paper is to encourage the search for accessible language features and teaching and learning facilitators which can ease the way into German as a Foreign Language (DaF). The paper begins with a terminological discussion, followed by a first model of the most important factors concerning the initial entry into FL territory. After a short review on previous work in this area, I consider methods for utilising knowledge of accessible language features and teaching and learning facilitators. Finally, suspected facilitating features - which have come to light through research as well as classroom observations – are exemplified. These, however, are to be understood as working hypotheses and thus still ’under construction’. Through this paper, I would like to invite other researchers to consider a new perspective on DaF with the intention of changing the status quo: "Applied linguistics is not simply a matter of matching up findings about language with pre-existing problems but of using findings to explore how the perception of problems might be changed. It may be that when problems are reformulated from a different point of view they become more amenable to solution. This changed perception may then, in turn, have implications for linguistics." (Cook : 2003: 10) My goal will have been achieved when the focus of this paper becomes a motivation for improving DaF teaching ("problems [...] become more amenable to solution") - and, should it lead to "implications for linguistics", so much the better. Ziel dieses Beitrages ist, eine umfassende Suche nach leichten Stellen und Erleichterungen beim Zugang zum Deutschen als fremder Sprache anzuregen. Nach Begriffsklärung und einem ersten Vorschlag zu den für die Zugänglichkeit einer Sprache ausschlaggebenden Faktoren (1) sowie einem kurzen Überblick über Fundstücke zum Thema (2) steht die Rolle der praktischen Umsetzung von Erkenntnissen als Hauptinstrument für den Bereich der Erleichterungen und die Nutzung leichter Stellen im Mittelpunkt (3). Dabei werden einige Kandidaten benannt, die sowohl aus vorliegenden Forschungsergebnissen als auch aus Beobachtungen in Alltag und Fremdsprachenunterricht (FSU) gewonnen wurden. Die so gewonnenen Einsichten sind als Arbeitshypothesen und somit als im Wandel begriffen zu verstehen. Ich möchte mit diesem Beitrag einladen zu einer neuen Perspektive auf das Deutsche als Fremdsprache, und zwar mit der Absicht etwas zu verändern: "Applied linguistics is not simply a matter of matching up findings about language with pre-existing problems but of using findings to explore how the perception of problems might be changed. It may be that when problems are reformulated from a different point of view they become more amenable to solution. This changed perception may then, in turn, have implications for linguistics." (Cook : 2003: 10) Mein Ziel ist erreicht, wenn sich vorliegende Fragestellung als Schlüssel zu verbesserter DaF-Unterrichtspraxis ("problems [...] become more amenable to solution") erweist. Falls sie sogar "implications for linguistics" zeitigt, umso besser.